Hospital at Home – an emerging opportunity for internal medicine trainees - Stephanie Moore; Rebekah Schiff; Daniel S. Furmedge (Future Healthcare Journal)
Hospital at Home (HAH) is growing at pace in the UK and is an acute clinical service that takes staff, equipment, technologies, medication and skills usually provided in hospitals and delivers that hospital care to selected people in their homes or in nursing homes. Services are as yet mostly excluded from doctors’ core training rotations. In parallel, non-traditional training pathways are being created to allow doctors to meet competencies outside of higher specialty training programmes. Evaluation of working in HAH as part of a locally designed internal medicine equivalence programme was undertaken, with specific focus on whether internal medicine curriculum competencies could be obtained. HAH provides valid internal medicine training, offering unique opportunities in clinical decision making, risk management, multidisciplinary team working, palliative medicine, and core internal and geriatric medicine. Reduced exposure to specific procedural skills and resuscitation in HAH can be mitigated across a balanced training programme. As HAH services develop, inclusion of HAH within internal medicine training programmes is recommended, alongside further research into their potential as a training environment.